The effect of flower-like tatania towards characteristics and performance of polysulfone mixed matrix membrane - Azhar, Mohd Faiz Hafeez (2018)
For ages, the polymeric membrane such as PSf is widely used in liquid separation for various application as the polymer itself offer versatile and attractive properties. However, due to strong hydrophobic nature of PSf property that create serious fouling problem to most of the separation process, thus modification of membrane by integrating strong hydrophilic particles is always practically used among industries and researchers. In this research, the effect of FLT as an additive in the PSf membrane was investigated. With consideration of the FLT that offer larger specific surface area as compared to ST that able to generate better performances and properties of polymer MMM. In this work, the polymer MMM of PSf/FLT and PSf/ST membranes were prepared via phase inversion method at five different concentrations of additive. Membrane characterization involved several observations such as cross-section area, particle distribution, surface roughness, hydrophilicity property, mean pore size, mechanical strength and porosity. Meanwhile, membrane performances were evaluated in terms of HA rejection, PWF, antifouling, antibacterial activity and photocatalytic properties based on self-cleaning antifouling efficiency. From the result, the addition of FLT was strongly influenced overall structure and characteristics of the membrane compared to ST. With a larger surface area of FLT and homogenous distribution inside membrane structure have resulted in better hydrophilicity effect thus improved the membrane performances. The PWF result was increased from 61.33 L/m2h to 137.81 L/m2h for PSf/ST and 155.46 L/m2h for PSf/FLT as increased additive to 3 wt%. Same results were obtained by rejection analysis where the PSf/FLT membrane able to reject more than 96% of HA and improved antifouling and self-cleaning efficiency. It is clearly shown that the present of higher specific surface area of FLT has improved overall characteristics and performances of the membrane compared to ST especially at 3 wt% of concentration.